Caffeine: Potential risks to health and positive drug testing - Harris, L. (2001)
In recent months there has been grave concern for the increasing use of so called "energy drinks" among swimmers, who do not realise the damage they are doing. These drinks contain large amounts of caffeine which is a drug. Dr Lenn Harris has provided some shocking facts on the effects of "energy drinks".